dada a função y=2x-3 determine
f (-2)
Soluções para a tarefa
Respondido por
1
y = f(x) = 2x - 3
Então, f(-2) é -2 calculado na função. Isto corresponde a
f(-2) = 2(-2) - 3
f(-2) = - 4 - 3 = -7
f(-2) = -7
Prova Real
![-7 = 2x - 3\\
2x = -7 + 3\\
2x = -4\\
x = \dfrac{-4}{2}\\\\
x = -2 -7 = 2x - 3\\
2x = -7 + 3\\
2x = -4\\
x = \dfrac{-4}{2}\\\\
x = -2](https://tex.z-dn.net/?f=-7+%3D+2x+-+3%5C%5C%0A2x+%3D+-7+%2B+3%5C%5C%0A2x+%3D+-4%5C%5C%0Ax+%3D+%5Cdfrac%7B-4%7D%7B2%7D%5C%5C%5C%5C%0Ax+%3D+-2)
Então, f(-2) é -2 calculado na função. Isto corresponde a
f(-2) = 2(-2) - 3
f(-2) = - 4 - 3 = -7
f(-2) = -7
Prova Real
victor1120:
Obrigado
Respondido por
0
f(x)=2x-3
f(-2)=2.(-2)-3
f(-2)=-4-3
f(-2)=-7
f(-2)=2.(-2)-3
f(-2)=-4-3
f(-2)=-7
Perguntas interessantes
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Português,
11 meses atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás